1983
DOI: 10.1364/ao.22.003701
|View full text |Cite
|
Sign up to set email alerts
|

Water-vapor continuum CO_2 laser absorption spectra between 27°C and −10°C

Abstract: Water continuum CO2 laser absorption spectra are reported for temperatures between 27 and -10 degrees C. The continuum is found to possess a negative temperature coefficient. The results obtained suggest that the magnitude of this temperature coefficient increases with increasing water pressure and decreasing temperature. The temperature coefficients between 27 and 10 degrees C for air mixtures containing 3.0- and 7.5-Torr water vapor are -2.0 +/- 0.4 and -2.9 +/- 0.5%/ degrees C, respectively. For mixtures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…In the majority of laboratory measurements of the water-nitrogen continuum in the 1000 cm −1 window, a tunable CO 2 -laser was used as a radiation source, and the P(20) transition at 944.2 cm −1 was the most popular in those investigations. It can be seen from the figure that the measurements of Nordstrom et al [18], Loper et al [20] and Cormier et al [15] agree with each other and provide the foreign continuum value of about 6 × 10…”
Section: Water-nitrogen Continuum Absorption In the 1000 CM −1 Atmospsupporting
confidence: 69%
See 2 more Smart Citations
“…In the majority of laboratory measurements of the water-nitrogen continuum in the 1000 cm −1 window, a tunable CO 2 -laser was used as a radiation source, and the P(20) transition at 944.2 cm −1 was the most popular in those investigations. It can be seen from the figure that the measurements of Nordstrom et al [18], Loper et al [20] and Cormier et al [15] agree with each other and provide the foreign continuum value of about 6 × 10…”
Section: Water-nitrogen Continuum Absorption In the 1000 CM −1 Atmospsupporting
confidence: 69%
“…These authors reported measurements with both a long path cell and spectrophone techniques at 26 CO 2 -laser transitions. Some of the results seem to have significant local line contribution to the absorption, as it is in the case of measurement on the R (20) 975.93 and R(14) 971.93 cm −1 transitions (see table 1 from Peterson et al [19]). In some other cases, the water vapour continuum absorption coefficients obtained with the opto-acoustic detector significantly deviate from measurements with the multi-pass cell.…”
Section: Water-nitrogen Continuum Absorption In the 1000 CM −1 Atmospmentioning
confidence: 85%
See 1 more Smart Citation
“…In Fig. 12, we show a comparison for the temperature dependence of the self absorption coefficient at frequencies near 1203 cm~' with experimental data obtained by a number of researchers using different experimental techniques (Burch et al, 1971;Montgomery, 1978;Loper et al, 1983). Also shown are some data from Varanasi (1988b) for a frequency near 1000 cm~'.…”
Section: Computational Results Of the Water Continuum Absorptionmentioning
confidence: 84%
“…Roberts et al (1976) derived an analytic expression for the continuum in the 8-13 /im region by fitting the data of Burch et al (1971Burch et al ( , 1974Burch et al ( , 1975. This formulation is still widely used because of its simplicity, but it does not reproduce the improved experimental laboratory data of Burch and co-workers (1982Burch and co-workers ( , 1984Burch and co-workers ( , 1985, nor does it model correctly the temperature dependence observed by Montgomery (1978) and by Loper et al (1983). Thomas and Nordstrom (1980, 1982a,b, 1985 sought to model the continuum absorption in terms of a modified line shape.…”
Section: Introductionmentioning
confidence: 99%